Seismic Analysis of Multi-Storey Building with Floating Columns Using Etabs - Prashant Diwan; Dushyant Sahu (International Journal of Scientific Research in Civil Engineering, 2022)
Now a day multi-storey buildings are constructed for the purpose of residential, commercial etc., with open ground storey is becoming common feature. For the purpose of parking all, usually the ground storey is kept free without any construction except columns. Buildings which have discontinuity of columns and building having columns which transfer load to the beams in lateral direction are called as floating column building. A column is meant to be an upright member ranging from footing level and conveying the load to the lowest. The term floating-column is additionally an upright member that ends (due to subject field design/ web site situation) at its lower level (termination Level) rests on a beam that may be a horizontal member. The beams successively transfer the load to alternative columns below it. Such columns in structures will be analyzed and designed. Results are compared in the form of Storey displacements, Storey Shear, Storey Drift, Lateral Load, Base shear, Modal Participation Ratio with & without columns. Also the Zone wise results are compared using tables & graph to find out the most optimized solution. ETABS 2018 has been utilized for analyzing the above Building Structure.